Big Data and Big Data Analytics: Basic Concept and Perspectives: Exploring the States and Perspectives of Big Data Analytics (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This study focuses on the various states ofstudies towards Big Data analytic techniques and gives a better comparativeanalysis of various applications. Inference has been done for evaluating theperformance efficiency, limitations and the advantages of the different typesof existing Big Data Analytic techniques. In the recent times the amount ofdata are generated and stored by various industries are rapidly increasing onthe internet thus data scientists are facing a lot of challenges formaintaining a huge amount of data as the fast growing industries require thesignificant information for enhancing the business and for predictive analysisof the information.  A larger amount ofdata gives a better output but also working with it can become a challenge dueto processing limitations. This paper intends to define the concept of Big Dataand stress the importance of Big Data Analytics.